Leucine Regulates Zoosporic Germination and Infection by Phytophthora erythroseptica - Jiang, He; Hwang, Hye Weon; Ge, Tongling; Cole, Barbara; Perkins, Brian; Hao, Jianjun (Frontiers in Microbiology, 2019)
Pink rot (Phytophthora erythroseptica) of potato is a major concern in many potato production regions. The pathogen produces zoospores that serve as a primary inoculum for infection. To understand how the pink rot incidence is related to pathogen population, qualitative and quantitative chemical analyses were conducted. It was demonstrated that P. erythroseptica zoospores required a minimal population of 103 zoospores/ml (threshold) for initiating germination and the subsequent infection; the percentage of zoosporic germination was positively correlated with the density of zoospores above the threshold. To elucidate the density-dependent behavior, zoospore exudate (ZE) was extracted from high-density (105/ml) zoospore suspension. Zoosporic inocula of P. erythroseptica at different concentrations were inoculated on potato tubers. Necrotic lesions were caused by inoculum with 100 zoospores per inoculation site; 5 zoospores per site did not cause lesions on the tuber. However, 5 zoospores did cause lesions when they were placed in ZE, suggesting ZE contained chemical compounds that regulate germination of zoospores. ZE was collected and analyzed using liquid chromatography mass spectroscopy (LC-MS). Results showed that the amino acid leucine was associated with zoosporic germination. Therefore, zoosporic germination and infection of P. erythroseptica were mediated by signaling molecules secreted from zoospores.